A Distributive Aboriginal Political Culture is Alive and Well in Northern Saskatchewan - Beatty, Bonita (Journal of Aboriginal Economic Development, 2016)
Many suggest that northern Aboriginal political culture has largely been lost due to political and economic colonization. This paper suggests otherwise. Based on research findings from a northern political engagement study, it argues that northern Aboriginal political culture remains strong despite the pressures of modern life. At a recent meeting, Indigenous Alumni from the Masters in Northern Governance and Development (MNGD) Program went a step further suggesting that while northern Aboriginal culture was resilient, it needed support in many areas including language retention, training, youth education and protection of local knowledge. It was suggested that a formalized network of Northern Aboriginal Scholars could provide significant support. Aboriginal Peoples in northern Saskatchewan developed a distinct 'way of life' in that region blending historical cultural values and a mixed-wage economy. Over 86% of the 37,000 people living in the 45 northern Saskatchewan communities (municipalities, reserves) are Woodland Cree, Dene and Métis peoples. The north is their traditional homeland. Findings from a three-year research study (2010-2013) on northern Aboriginal political engagement illustrated a high desire (96.3%) by Indigenous people to protect their traditional northern ways of life (hunting, trapping, fishing, gathering) and the distributive values associated with it. This and other findings suggest that Aboriginal political culture in northern Saskatchewan is changing but is still alive and well.